Best Answer

It is: 3x2+6x-11 = 0

Q: What is 3x squared plus 6x-3 equals 8 in the form of Ax squared plus Bx plus C equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x3 - x2 + 17 = 2x2 + 47 6x3 - x2 - 2x2 = 47 - 17 x2(6x - 1 - 2) = 30 this is the simplest factorisation.

10x + 8x - 6x3 + 4x2 + 12x3 - x add the like terms. all the x's are like terms. al the x squared are like terms. all the x cubed are liked terms. 6x3 + 12x2 + 9x

6x3+29x2-40x-42 divided by 6x+5 Quotient: x2+4x-10 Remainder: 8

We're on it . . .6x3 + 4x2 = 2xSubtract 2x from each side:6x3 + 4x2 - 2x = 0Divide each side by 2:(Don't divide by 'x' ... you'll lose a root.)3x3 + 2x2 -x = 0Factor the left side:x (3x2 + 2x - 1) = 0x (3x - 1) (x + 1) = 0x = 0x = 1/3x = -1

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)

Related questions

6x3 - x2 + 17 = 2x2 + 47 6x3 - x2 - 2x2 = 47 - 17 x2(6x - 1 - 2) = 30 this is the simplest factorisation.

10x + 8x - 6x3 + 4x2 + 12x3 - x add the like terms. all the x's are like terms. al the x squared are like terms. all the x cubed are liked terms. 6x3 + 12x2 + 9x

You don't know that?! If x=3, then 6x is 6x3. So 18 plus 2 is.....20!!

-6x3 + 4x7 - 0.8x2 + x4 - 5x5 = 4x7 - 5x5 + x4 - 6x3 - 0.8x2 = x2 (4x5 - 5x3 + x2 - 6x - 0.8)

The answer is 37.

-20

6x3 - 27x2 + 3x + 36 = 3 (x - 4) (x + 1) (2x - 3)

6x3+29x2-40x-42 divided by 6x+5 Quotient: x2+4x-10 Remainder: 8

18x1, 9x2, 6x3, 12x1.5, etc

2x3

We're on it . . .6x3 + 4x2 = 2xSubtract 2x from each side:6x3 + 4x2 - 2x = 0Divide each side by 2:(Don't divide by 'x' ... you'll lose a root.)3x3 + 2x2 -x = 0Factor the left side:x (3x2 + 2x - 1) = 0x (3x - 1) (x + 1) = 0x = 0x = 1/3x = -1

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)